2020
DOI: 10.1186/s12860-020-00295-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and machine learning analysis of Abemaciclib in colon cancer

Abstract: Background: The main challenge in cancer research is the identification of different omic variables that present a prognostic value and personalised diagnosis for each tumour. The fact that the diagnosis is personalised opens the doors to the design and discovery of new specific treatments for each patient. In this context, this work offers new ways to reuse existing databases and work to create added value in research. Three published signatures with significante prognostic value in Colon Adenocarcinoma (COAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The synergistic effect was pronounced when abemaciclib was combined with LY3009120, a pan-raf inhibitor (64). Using machine learning to identify the prognostic signature of colon adenocarcinoma, Linares-Blanco et al found that several genes are potential candidates for therapeutic targeting including fatty acid binding protein 6 (FABP6) (65). The in silico molecular docking revealed that FABP6 strongly interacted with abemaciclib.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The synergistic effect was pronounced when abemaciclib was combined with LY3009120, a pan-raf inhibitor (64). Using machine learning to identify the prognostic signature of colon adenocarcinoma, Linares-Blanco et al found that several genes are potential candidates for therapeutic targeting including fatty acid binding protein 6 (FABP6) (65). The in silico molecular docking revealed that FABP6 strongly interacted with abemaciclib.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, the FABP6 gene has greater specificity for abemaciclib when compared with others. Therefore, this study suggested that abemaciclib targeting FABP6 has the potential to be a therapeutic target and needs further experimental validation[ 99 ]. Consequently, our research group applied a DR strategy by targeting the coexpression network of the protein Multidrug Resistance 1 (MDR1) expressed by the ABCB1 protein that causes chemotherapy failure.…”
Section: Drmentioning
confidence: 99%
“…Current advances in Pathomics tissue analytics are focused on predicting the biological behavior of human disease and cancer for precision medicine applications. One of the main challenges in Pathomics is to identify the types of data products that can be useful to identify patterns, relationships, or biomarkers to provide clinically actionable information [42]. Current Pathomics applications are incredibly powerful and useful for understanding how and why the dynamic microscopic landscapes of tissues change during the initiation and progression of disease.…”
Section: Tumor Immune Interactions With Pathomicsmentioning
confidence: 99%